(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Metaphor is one of the most effective mental and linguistic forms of knowing and describing the world. Metaphor plays a special role in expressing abstract concepts, including "love", because it makes it easier to understand complex emotions. The article provides information about the basics of similes in the formation of metaphorical models with the concept of "love" in English and Uzbek languages, and briefly touches on the definition of metaphors and similes in linguistics.